Serological study of toxoplasmosis spread among unmarried female university students using LAT, ELISA and IgG avidity - Baghdad Science Journal (مجلة بغداد للعلوم)
Toxoplasma gondii has a worldwide distribution and it is one of the most prevalent infectious agents in Iraq. The study was conducted on 200 serum samples of unmarried female university of students age ranged between 18 to 26 years to detect Toxoplasma gondii antibodies. The aim of this study was to detect T. gondii antibodies among unmarried female students in Iraqi universities using different serological tests. Seventy six (38%) serum samples out of 200 subjects were positive for toxoplasma antibodies by Latex agglutination test (LAT). Among 76 LAT sera positive ,only 58 (29%) serum samples were positive with toxoplasma IgG ELISA test , however , the results of IgM ELISA assay were positive only for 3 (1.5%) unmarried female sample .None of negative LAT serum samples gave positive results with neither IgG nor IgM ELISA.